Description of Implementation of Agricultural Learning at Farmers Fajar Menyingsing Group at Pasaman - Nuraina Nuraina; Syuraini Syuraini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
Researchers suspect the cause of increased crop yields is due to the implementation of learning in good agricultural extension by the Farmers Fajar Menyingsing group. This research aims to see an overview of the Implementation of Agricultural Counseling Learning in terms of aspects of learning material and aspects of learning methods. This type of research is quantitative descriptive research. The population in this study were 30 members of the Farmers Fajar Menyingsing group. Samples were taken as much as 75% of the entire Farmers Fajar Menyingsing group, totaling 30 people. The data collection technique in this study was a questionnaire, while the data collection tool was a questionnaire. Data analysis techniques using the percentage formula. The results of the study showed that the description of the implementation of farmer group counseling learning in the Dawn of Judging in terms of learning material aspects was already in the good category, this indicates that the learning citizens could understand the learning material conveyed by the instructor. An overview of the implementation of agricultural extension learning Farmers Fajar Menyingsing group in terms of aspects of learning methods are already in the good category, this indicates that learning citizens can understand the learning material provided by instructors with interesting learning methods, the suitability of the material with the method, and the effectiveness of the use of learning methods.Keywords: Implementation, Learning, Success